A SIAD achievement based on the collection of the industry costs - TOFAN, Cezarina Adina (Annals of Spiru Haret University. Economic Series, 2014)
In modern market economy, organizations have to take decisions in a flexible, dynamic manner. In the economic environment, the relationship between product - market and competition is becoming more and more complex, as the socio-economic environment itself becomes more diversified and complex. Thereby, in order to be efficient, the management has to rely not only on chance and inspiration but especially on scientific methods designed to resolve dilemmas and multiple choice situations. The decision-making process represents an complex sum of activities regarding the collection, processing and selection of information. The information becomes a valuable asset for the organization if it is obtained and used in real-time, therefore the decision making process is highly dependent on complex, operational and qualitative information.